Enhanced Antitumor Efficacy and Reduced Toxicity in Colorectal Cancer Using a Novel Multifunctional Rg3- Targeting Nanosystem Encapsulated with Oxaliplatin and Calcium Peroxide - Xie Y; Zhu M; Bao H; Chen K; Wang S; Dai J; Chen H; Li H; Song Q; Wang X; Yu L; Pei J (International Journal of Nanomedicine)
Yizhuo Xie,1 Ming Zhu,1 Han Bao,1 Kejia Chen,1 Shanshan Wang,1 Jingwen Dai,1 Hongzhu Chen,1 He Li,1 Qi Song,2 Xinlu Wang,2 Liangping Yu,2 Jin Pei1 1Department of Biopharmacy, School of Pharmaceutical Sciences, Jilin University, Changchun, People’s Republic of China; 2Department of Clinical Pharmacy, the First Hospital of Jilin University, Changchun, People’s Republic of ChinaCorrespondence: Jin Pei, Department of Biopharmacy, School of Pharmaceutical Sciences, Jilin University, No. 1163 Xinmin Street, Changchun, 130021, People’s Republic of China, Tel +86-431-85619725, Email peijin@jlu.edu.cn Liangping Yu, Department of Clinical Pharmacy, the First Hospital of Jilin University, No. 1 Xinmin Street, Changchun, 130061, People’s Republic of China, Tel +86 431 81879802, Email liangpingyu@jlu.edu.cnPurpose: Colorectal cancer (CRC) is the second leading cause of cancer-related deaths worldwide. Oxaliplatin (OXA) is currently the primary chemotherapeutic agent for CRC, but its efficacy is limited by the tumor microenvironment (TME). Here, we present a combined approach of chemotherapy and TME modulation for CRC treatment. A multifunctional nanosystem (Rg3-Lip-OXA/CaO2) was established using Ginsenoside Rg3 liposomes targeting glucose transporter 1 overexpressed on the surface of CRC cells to co-deliver OXA and calcium peroxide (CaO2).Methods: The CaO2 nanoparticles were synthesized via the CaCl2-H2O2 reaction under alkaline conditions and characterized using X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). Rg3-Lip-OXA/CaO2 was prepared through a thin-film hydration approach and characterized; additionally, its stability and release behavior were studied. The O2, H2O2, and Ca2+ generation ability of Rg3-Lip-OXA/CaO2 in solution and HCT116 cells were measured. The in vitro cellular uptake was observed via fluorescence microscope and flow cytometry. In vitro cytotoxicity was evaluated using the CCK-8 assay, flow cytometry, and live/dead cell staining. The in vivo targeting effect as well as antitumor efficacy were determined in HCT116 tumor-bearing mice. Finally, the acute toxicity of Rg3-Lip-OXA/CaO2 was investigated in ICR mice to explore its safety.Results: The XRD and XPS analyses confirmed the successful synthesis of CaO2 nanoparticles. The Rg3-Lip-OXA/CaO2 exhibited an average particle size of approximately 92.98 nm with good stability and sustained release behavior. In vitro and in vivo studies confirmed optimal targeting by Rg3-Lip and demonstrated that the nanosystem effectively produced O2, H2O2 and Ca2+, resulting in significant cytotoxicity. Additionally, in vivo studies revealed substantial tumor growth suppression and reduced tumor-associated fibroblasts (TAFs) and collagen. Acute toxicity studies indicated that Rg3-Lip-OXA/CaO2 markedly reduced the toxicity of chemotherapeutic drugs.Conclusion: This multifunctional nanosystem enhances chemotherapy efficacy and reduces toxicity, offering a promising approach for optimizing CRC treatment and potential clinical application. Keywords: tumor microenvironment, multifunctional nanosystem, oxaliplatin, calcium peroxide, targeted drug delivery, anticancer therapy